Memahami Strategi Pengelolaan Keuangan pada Usaha Kecil Menengah di Kota Amuntai: Studi Kasus pada Industri Kuliner - Ary Yudianto (JURNAL BISNIS DAN PEMBANGUNAN, 2024)
Abstract: This study aims to understand the financial management strategies implemented by Small and Medium Enterprises (SMEs) in the culinary sector in Amuntai City, as well as the challenges they face in maintaining financial stability. The culinary SMEs in Amuntai play a significant role in supporting the local economy. However, limited financial literacy and access to capital are major obstacles to business sustainability. This research employs a descriptive qualitative approach through in-depth interviews with SME owners and observation of the financial practices they carry out. The results show that most SMEs manage their finances in a simple manner, yet they face challenges in cash flow management, budget planning, and transaction recording. The recommendations generated include improving financial literacy, financing access, and utilizing simple technologies to support better financial recording. These findings are expected to provide insights for business actors and stakeholders in formulating policies that support the growth of culinary SMEs in Amuntai